Symbolic meanings of Peter Bevza’s creativity - S. P. Stoian (Ukrainian Cultural Studies, 2020)
In the technocratic labyrinths of the modern metropolis, the human requests of the Other are partially dissolved in the chaotic, stormy space of ubiquitous commotion.